Practice model: Establishing and running an oral chemotherapy management clinic - Paige May; Kourtney LaPlant; Ashley McGee (Elsevier, 2017)
Oral anticancer agents, while potentially more convenient and better tolerated than traditional intravenous therapy, come with significant concerns of noncompliance, adverse effects, and high cost. This presents an opportunity for health-care practitioners to develop a method to educate and support patients who are placed on these agents. To provide a detailed example of a currently established oral chemotherapy clinic and provide direction toward setting up a new clinic at other institutions. A description of the establishment of the clinic, how it is run and examples of interventions are provided. Establishment of an oral chemotherapy clinic run by supportive oncology practitioners is feasible and may provide added value to existing oncology care. It can also provide an opportunity to further involve health-care trainees in patient care.